Convergent validity and stability of secure base script knowledge from young adulthood to midlife. Issue 5 (3rd September 2021) - Waters, Theodore E. A.; Facompré, Christopher R.; Dagan, Or; Martin, Jodi; Johnson, William F.; Young, Ethan S.; Shankman, Jessica; Lee, Yoojin; Simpson, Jeffry A.; Roisman, Glenn I.
ABSTRACT: Attachment theory posits that early experiences with caregivers are made portable across development in the form of mental representations of attachment experiences. These representations, the secure base script included, are thought to be stable across time. Here, we present data from two studies. Study 1 ( N = 141) examined the degree of empirical convergence between the two major measures of secure base script knowledge in Study 2, we examined stability of secure base script knowledge from late adolescence to midlife combining data from both a high- and normative-risk cohort ( N = 113). Study 1 revealed evidence for convergent validity ( r = .50) and Study 2 revealed moderate rank-order stability ( r = .43), which was not moderated by cohort risk status. Results support the validity of secure base script knowledge assessments and prediction that attachment representations show moderate stability across early adulthood and into midlife.